Multiscale solid mechanics strength, durability, and dynamics - Altenbach, Holm 1956-; Eremeyev, Victor A.; Igumnov, Leonid A. (Advanced Structured Materials, 2021)
This book provides an overview of the current of the state of the art in the multiscale mechanics of solids and structures. It comprehensively discusses new materials, including theoretical and experimental investigations their durability and strength, as well as fractures and damage